2014
DOI: 10.1073/pnas.1421815112
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist of GH-releasing hormone receptors alleviates experimental ocular inflammation

Abstract: Disruptions in immunity and occurrence of inflammation cause many eye diseases. The growth hormone-releasing hormone-growth hormone-insulin-like growth factor-1 (GHRH-GH-IGF1) axis exerts regulatory effects on the immune system. Its involvement in ocular inflammation remains to be investigated. Here we studied this signaling in endotoxin-induced uveitis (EIU) generated by LPS. The increase in GHRH receptor (GHRH-R) protein levels was parallel to the increase in mRNA levels of pituitary-specific transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 40 publications
(41 reference statements)
10
40
0
Order By: Relevance
“…Outside the pituitary, the GHRH-GH pathway also functions in normal and neoplastic peripheral tissues, and is mediated by, among others, insulin-like growth factor-1 (11). We have previously shown that GHRH-R antagonists play protective roles in the rat eye, suggesting that GHRH-R antagonists are potential therapeutic agents for ocular inflammation (12). Notably, we also found detectable levels of GHRH, GHRH-R, and…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Outside the pituitary, the GHRH-GH pathway also functions in normal and neoplastic peripheral tissues, and is mediated by, among others, insulin-like growth factor-1 (11). We have previously shown that GHRH-R antagonists play protective roles in the rat eye, suggesting that GHRH-R antagonists are potential therapeutic agents for ocular inflammation (12). Notably, we also found detectable levels of GHRH, GHRH-R, and…”
supporting
confidence: 56%
“…GHRH-R expression in other human ocular tissues has not been reported to our knowledge. In our previous study in rats, GHRH-R could be detected in cornea, iris, and ciliary body (12). In addition to the GHRH-R expression, whether Y79 cells express its ligand GHRH is currently unknown.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MIA-602 inhibited NF-κB in glioblastoma, breast cancer, and ovarian cancer (37). Most recently, MIA-602 was shown to inactivate STAT3 in mouse bone marrow-derived mesenchymal stem cells (50) and to down-regulate the expression of inflammatory cytokines in experimental ocular inflammation (38) and triplenegative breast cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory effects for GHRH antagonists were also demonstrated in experimental models of cancer and ocular inflammation (39,40).…”
Section: Significancementioning
confidence: 93%